Analisis Laporan Keuangan sebagai Alat Penilaian Kinerja Keuangan pada Koperasi Samudra Mulya Ciparagejaya-Karawang 2013-2018 - Nisa Syahidah; R. Aditya Kristamtomo Putra (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2020)
Marine Fisheries Cooperativies production called KPPL a financial institution to empower the fishermen and help the economy of the fishermen arround. But many cooveratives / KPPL experienced significant tidal cooperative as a bussines entity that is differnt, has a special indikator in determining achievement performance.This research is descriptive research, which in this study describes and explain how the financial performance of the cooverative KPPL Samudra Mulya using financial statements as the basis for the financial perfomance of assesment. It’s this, this study aimed to analize the financial performance of the Marine Fisheries Cooperativies Production (KPPL) Samudra Mulya. Bassed on these results we concluded a brief presentation of pinancial statements Marine Fisheries Production Cooperatives “KPPL” consisting of banlance sheet income statements, statements of changes in equity, cash flow statements and notes on financial statements. Financial statement analysis is a relationship between one another with both quantitative and non-quantitative data explaining changes in financial conditions to determine a decision to be taken.